Factors affecting Yemen higher education institutions performance: Challeneges and obstacles - Al-haimi, Basheer; Hamid, A. B.; Hujainah, Fadhl (Science Publishing Corporation, 2018)
Yemen's higher education institutions face unmatched circumstances and challenges. Yemen’s higher education institutions encounter a lot of obstacles and issues that affect its performance of being competitive among other institutions of the same region or the rest of the world. Therefore, this paper investigates current obstacles and factors that affect the performance of higher education intuitions of Yemen that results them for not being listed among World Class Universities. This study employs qualitative method, where 5 experts and experienced people are interviewed. The findings of this study showed that, lack of national vision of government, leadership, financial support, research and development funding, autonomy, governance, academic staff development, ratio of student’s enrollments in humanity studies and quality of academic programs are some of the major issues that the Yemen higher education institutions currently experience. It is hoped that, through this article, the HEIs of Yemen would be enhanced and improved by concentrating and finding the best solutions in order to propel and be able to leap to a greater height in the region.v